Decision-making model of sustainable ecological environment management based on enterprise environmental management under a low-carbon economy - Li, Xiaoao; Gao, Jiangang (Frontiers in Energy Research, 2023)
With the continuous advancement of the industrialization process, the production and operation activities of enterprises are also continuing. Many enterprises are making great efforts to develop the economy. At the same time, they ignore the ecological environment problems, causing serious damage to the ecological environment. In addition, the treatment of agricultural waste is too rough, and the direct burning of crop straw and livestock manure has caused more serious damage to the ecological environment. From the perspective of low-carbon economy, in order to promote the sustainable development of the ecological environment, this paper proposes to integrate the enterprise's environmental management concept, establish an ecological environment management decision-making model, and carry out relevant research on the ecological environment management decision-making model of the Yangtze River basin with the method of system dynamics. The experimental results showed that the average error of section water quality prediction was 2, the average error of pollutant discharge prediction was 2.1, and the highest ecological security degree was 1.28. It can be seen from the above data that the system dynamics method can effectively reduce the section water quality prediction error and pollutant discharge prediction error of the management decision-making model, and improve the accuracy of the model prediction. In the analysis experiment of biomass energy potential of agricultural waste, livestock manure and straw waste accounted for 59.26% and 30.18% of the total, respectively. It can be seen that agricultural waste has a high content of biomass energy that can be converted and can provide a large amount of renewable energy for human beings.